2001
DOI: 10.1071/ar01054
|View full text |Cite
|
Sign up to set email alerts
|

Grain proteins as markers of genetic traits in wheat

Abstract: Different protein fractionation techniques were used to define differences between a set of 8 wheat lines used in genetic mapping studies in Australia. A proteomics approach was used to establish the feasibility of identifying new protein polymorphisms for mapping purposes. Detailed analysis confirmed differences in the glutenin subunits, gliadin proteins, and 10–20 other proteins, between the mapping population parents, Cranbrook, Halberd, CD87, and Katepwa. Differences were particularly evident in the low mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Compared to the normal Bx7 gene, the gene conferring Bx7 overexpression has an 18 bp insertion in the central repetitive domain, a 43 bp indel of the 5′-region and the left and right junctions of the LTR retrotransposon borders and the duplicated segment, and has been used to developed PCR markers as well as high throughput KASP markers for differentiating these two genotypes [54,55] . Other allelic variants also have differential effects on dough quality, e.g., Glu-B1 subunits 17 + 18 are associated with strong dough while subunits 20x + 20y are associated with weak dough [56] . Statistical analysis of large numbers of durum wheat genotypes confirmed the strong correlation of g-gliadin 45 with good processing quality and g-gliadin 42 with poor processing quality.…”
Section: Wheat Gluten Protein Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the normal Bx7 gene, the gene conferring Bx7 overexpression has an 18 bp insertion in the central repetitive domain, a 43 bp indel of the 5′-region and the left and right junctions of the LTR retrotransposon borders and the duplicated segment, and has been used to developed PCR markers as well as high throughput KASP markers for differentiating these two genotypes [54,55] . Other allelic variants also have differential effects on dough quality, e.g., Glu-B1 subunits 17 + 18 are associated with strong dough while subunits 20x + 20y are associated with weak dough [56] . Statistical analysis of large numbers of durum wheat genotypes confirmed the strong correlation of g-gliadin 45 with good processing quality and g-gliadin 42 with poor processing quality.…”
Section: Wheat Gluten Protein Variationsmentioning
confidence: 99%
“…Moreover, loaf volume during the baking process has a negative relationship with acetic acid-soluble glutenin and a positive relationship with acetic acid-insoluble glutenin [11] . For extensibility, Cornish et al [56] suggested this was a more complex trait involving other parameters such as LMW-GS and gliadin compositions. However, gliadins appear to be less important in determining bread quality, and the addition of gliadins or the overexpression of certain gliadins can reduce dough strength [57] .…”
Section: Wheat Gluten Protein Variationsmentioning
confidence: 99%
“…This extract was then treated with 100 ml of 1.4% 4-vinylpyridine to alkylate the subunits and prevent the reformation of disulphide bonds. The extracts were subjected to onedimensional electrophoresis and stained as described in Cornish et al (2001a).…”
Section: Sds-page Analysis Of Hmw-gs Compositionmentioning
confidence: 99%
“…The LMW-GS are encoded by genes at the Glu-A3, Glu-B3 and Glu-D3 loci on the short arms of chromosome 1A, 1B and 1D, respectively (Gupta and Shepherd 1990). Although the HMW-GS are less abundant than the LMW-GS, they have a major impact on dough quality, are amenable to relatively straightforward analysis and therefore have been used extensively as markers in breeding programs (Cornish et al 2001a).…”
Section: Introductionmentioning
confidence: 99%
“…Although the HMW‐GS are less abundant than the LMW‐GS, they have a major impact on dough quality and are amenable to relatively straightforward analysis. They have been used extensively as markers in breeding programs (Cornish et al , ; Ma et al ).…”
mentioning
confidence: 99%